The Role of Soluble Costimulatory Molecules as the Biomarkers for Aging Predictors - Kusworini Handono; Mirza Zaka Pratama; Hani Susianti; Cesarius Singgih Wahono; Nimas Eka Firdaningrum; Siti Roziah Ria Famuji; Norma Hanifah Sumarta; Ade Wildan Rizky Fachry; Levrita Nindya Poetri; Handono Kalim (Fakultas Kedokteran Universitas Brawijaya, 2023)
This study aimed to determine the role of the soluble costimulatory molecules in aging and the association with the presence of comorbid in aged individuals. Thirty-two elderly and twenty healthy subjects were included in this study. The soluble costimulatory molecules sCD28, sCD80, sCD86, sCD163, and sCTLA4 were measured using ELISA. The presence of comorbid was documented from medical records. Charlson Comorbidity Index (CCI) was measured to evaluate the survival/mortality risk for the subjects. The levels of the majority of soluble costimulatory molecules significantly increased in the elderly participants, while the level of sCD86 was comparable. There were weak positive correlations between the subject's age and levels of sCD28 (R=0.214, p=0.048), sCTLA4 (R=0.238, p=0.041), and sCD80 (R=0.317, p=0.012). sCD80 were discovered to be the best to predict immune aging in the elderly with AUC 0.71 [0.57-0.86], sensitivity 53,1%, specificity 80.0%, and cut off 129ng/ml. Most of the elderly participants had at least one comorbid, in which approximately 25.0% and 3.1% of the subjects were classified as mild and moderate CCI. Multivariate analysis showed that comorbidities in elderly individuals have been associated with levels of sCTLA4 ≥26.5ng/ml and sCD80 ≥129.0ng/ml. Furthermore, subjects with comorbid (CCI ≥1) were associated with sCD80 ≥129.0ng/ml (OR 12.44 [95% CI 1.32–117.03], p=0.027). Considering these results, sCD28, sCTLA4, and sCD80 can be developed as biomarkers for predicting immune aging and elderly comorbidities, respectively.